2015
DOI: 10.1016/j.jtcvs.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Practice improves performance on a coronary anastomosis simulator, attending surgeon supervision does not

Abstract: Practice on low-fidelity simulators enabled trainees to improve on a broad range of skills; however, the additional effect of attending-level supervision is limited. In an era of increasing staff surgeon responsibilities, unsupervised practice may be sufficient for inexperienced trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Acknowledging the limitations of simulation-based training, the simulator can never mimic the feel of live human tissue and the complexity of human physiology. But it might serve as a crucial adjunct or bridge for the advanced technique, with a safer transition to daily clinical practice [Enter 2015;Mokadam 2017;Feins 2017;Ribeiro 2017;Ramphal 2005]. The simulation does not mimic the feel of living human tissue and the complexity of human physiology.…”
Section: E778mentioning
confidence: 99%
“…Acknowledging the limitations of simulation-based training, the simulator can never mimic the feel of live human tissue and the complexity of human physiology. But it might serve as a crucial adjunct or bridge for the advanced technique, with a safer transition to daily clinical practice [Enter 2015;Mokadam 2017;Feins 2017;Ribeiro 2017;Ramphal 2005]. The simulation does not mimic the feel of living human tissue and the complexity of human physiology.…”
Section: E778mentioning
confidence: 99%
“…Previous studies have demonstrated a relationship between operative efficiency and age, gender, American Society of Anesthesiologists score, and surgical team experience. [11][12][13][14] These findings could not be replicated in our study population, composed entirely of patients undergoing lung resection. However, our results corroborate the findings of a systematic review of general thoracic surgery procedures reporting that age, gender, tobacco use, and comorbidities (including American Society of Anesthesiologists score) had minimal or no significant impact on surgical times.…”
Section: Discussionmentioning
confidence: 64%
“…An instructional video was provided in three trials 5 , 14 , 17 . In person education sessions were provided in four trials 14 , 15 , 17 , 18 .…”
Section: Resultsmentioning
confidence: 99%